2017
DOI: 10.1186/s12944-017-0525-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholecystectomy on hepatic fat accumulation and insulin resistance in non-obese Hispanic patients: a pilot study

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is highly prevalent worldwide. Experimental studies have shown that cholecystectomy (XGB) increases hepatic fat content in mice and appears associated to NAFLD in large retrospective population-based studies. The aim of this study was to prospectively assess the effects of XGB on hepatic fat content (HFC) and insulin resistance (IR) in non-obese, middle aged Hispanic subjects.MethodsTwenty-six gallstone patients undergoing elective XGB and 16 control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
1
18
0
6
Order By: Relevance
“…Current prospective and retrospective studies suggest a strong association between cholecystectomy and NAFLD. [3,[10][11] Cholecystectomy was emphasized as an independent risk factor for NAFLD. [10,14] Furthermore, Shen et al…”
Section: Discussionmentioning
confidence: 99%
“…Current prospective and retrospective studies suggest a strong association between cholecystectomy and NAFLD. [3,[10][11] Cholecystectomy was emphasized as an independent risk factor for NAFLD. [10,14] Furthermore, Shen et al…”
Section: Discussionmentioning
confidence: 99%
“…Так, в энтеро-цитах и гепатоцитах активация фарнезоидного Х-рецептора (FXR) блокирует синтез желчных кислот из холестерина посредством инактивации цитохрома С450 (СYP27A1) и увеличивает экс-прессию переносчиков желчных кислот, что спо-собствует их энтерогепатической циркуляции. Взаимодействие желчных кислот с FXR L-клеток кишечника вызывает снижение экспрессии про-глюкагона и глюкагоноподобного пептида-1 (ГПП-1), регулирующих чувство насыщения [5]. Эффекты активации TGR5 (мембранного рецеп-тора желчных кислот) наиболее активно изуча-ются, и согласно известным механизмам влияния TGR5 желчные кислоты представляются регуля-торами углеводного и основного обменов, бло-каторами воспаления в ткани печени, эндотелии и жировой ткани, регуляторами функции щито-видной железы на периферии [9].…”
Section: Discussionunclassified
“…Анализ данных литературы показывает, что сочетание ЖКБ и НАЖБП имеет следующие особенности: у 55% пациентов с ЖКБ наблю-даются морфологические признаки НАЖБП, у 10% пациентов с ЖКБ отмечены выраженные фибротические изменения печени, а 19,8% па-циентов с НАЖБП страдают ЖКБ [5]. Более того, в общей популяции ЖКБ встречается у 13%, а в популяции с НАЖБП частота выяв-ления ЖКБ достигает 34,3%.…”
unclassified
“…We found that liver triglycerides, quantified by magnetic resonance imaging, were increased in two over four liver segments after 24 months of the surgery, whereas no changes were noted in control individuals during the same period of time. Similarly, HOMA‐IR index increased by approximately 70% after 24 months in patients with cholecystectomy whereas it remained unchanged in control patients . These results substantiate the hypothesis that the GB regulates hepatic triglyceride content and systemic insulin sensitivity in humans with GSD.…”
Section: Potential Roles Of the Gb On Glucose And Lipid Metabolism Anmentioning
confidence: 99%